PERENCANAAN STRATEGI PENINGKATAN KUALITAS PELAYANAN DENGAN MENGGUNAKAN SWOT DI RSUD XYZ - Muhammad Nur (Jurnal Teknik Industri Terintegrasi, 2020)
The decreasing of percentage from the patient RSUD XYZ is 5,13% than two years before. The lowest percentage from the visitor is in surgical poly 27,69% but it get increasing than years before to 33,56%. while the satisfying from the patient in this poly is only 40%. In this condition RSUD YZ to make special strategy to get best service of quality for the patient in poly. The method can be used is of SWOT analyze to give new strategy by got from the technic respon of SWOT matrix. This research use 25 variable service that need by patient. The matrix formation of service attribute â€œthe performance speed of nurses in taking measures to patinetâ€ has relative important value 5,163% so it can educations, training and development to nurses for at last 6 month as priority to increase the service. And than best strategy in increase the service in poly is by increasing the nurse skill, do the promotion healthy activity by medical check up packet, also have innovative and special service.